Unilateral biportal endoscopic decompression for lumbar spinal stenosis: a single-center experience with intraoperative neurophysiological monitoring - Minh Anh Nguyen; Anh Phung Ngo; Nhut Linh Nguyen (Interdisciplinary Neurosurgery, 2025)
Study Design: Retrospective Cohort Study. Objective: Previously, unilateral biportal endoscopic surgery was commonly used for herniated disc removal rather than spinal stenosis decompression. To evaluate the effectiveness and safety of unilateral biportal endoscopic surgery with intraoperative neurophysiological monitoring in the treatment of lumbar spinal stenosis, we conducted the study: “Unilateral biportal endoscopic surgery with intraoperative electrophysiology monitoring in lumbosacral spinal stenosis treatment”. Methods: Patients with lumbar spinal stenosis treated at the Department of Neurosurgery, University Medical Center, Ho Chi Minh City, Vietnam from January 2021 to December 2022 were included. The study subjects had to meet the following criteria: persistent radicular pain, lower limb weakness, or neurogenic claudication unresponsive to conservative treatment for at least 6 months, and MRI evidence of moderate to severe lumbar spinal stenosis at 1 or 2 levels. Results: Preoperatively, the VAS score for radicular pain was 5.6 ± 1.1 points, and for back pain was 4.7 ± 1.2 points, significantly reducing to 2.6 ± 0.8 points and 3.2 ± 0.8 points respectively (p < 0.001). Lumbar spine function significantly improved postoperatively with the ODI score decreasing from 50.3 ± 7.2 points preoperatively to 34.4 ± 6.2 points at the final evaluation (p < 0.001). Conclusion: Unilateral biportal endoscopic posterior decompression can be widely applied in clinical practice for the treatment of degenerative lumbar spinal stenosis. For increased surgical safety, it is recommended to equip operating rooms with intraoperative neurophysiological monitoring systems to enhance surgeon confidence and patient safety.